2018
DOI: 10.1097/mrr.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

The role of robotic gait training coupled with virtual reality in boosting the rehabilitative outcomes in patients with multiple sclerosis

Abstract: Motor impairment is the most common symptom in multiple sclerosis (MS). Thus, a variety of new rehabilitative strategies, including robotic gait training, have been implemented, showing their effectiveness. The aim of our study was to investigate whether an intensive robotic gait training, preceding a traditional rehabilitative treatment, could be useful in improving and potentiating motor performance in MS patients. Forty-five patients, who fulfilled the inclusion criteria, were enrolled in this study and ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 24 publications
0
60
0
2
Order By: Relevance
“…Various systematic reviews have demonstrated the efficacy of VR-based intervention as a home training method in the COVID-19 pandemic in patients with different neurological diseases, including MS [86,87]. Scientific evidence shows that home training based on VR is a therapy that provides motivation, and it can be useful in the rehabilitation of physical and cognitive function in PwMS [88]. The use of VR at home seems to have a positive impact as a method of support for traditional rehabilitation, especially during the COVID-19 pandemic, due to the difficulty of these patients accessing classical therapies in clinical centers [89].…”
Section: Discussionmentioning
confidence: 99%
“…Various systematic reviews have demonstrated the efficacy of VR-based intervention as a home training method in the COVID-19 pandemic in patients with different neurological diseases, including MS [86,87]. Scientific evidence shows that home training based on VR is a therapy that provides motivation, and it can be useful in the rehabilitation of physical and cognitive function in PwMS [88]. The use of VR at home seems to have a positive impact as a method of support for traditional rehabilitation, especially during the COVID-19 pandemic, due to the difficulty of these patients accessing classical therapies in clinical centers [89].…”
Section: Discussionmentioning
confidence: 99%
“…Doniger et al showed that VR is a useful tool in cognitive and motor rehabilitation of patients with Alzheimer's disease [30]. These positive results were also confirmed in patients with multiple sclerosis, as 2D VR was able to further boost neural plasticity and thus functional recovery [31]. A recent pilot study performed on individuals with Parkinson's disease found that VR improved cognitive functions, with regard to executive and visuospatial domains, besides mood [32].…”
Section: Discussionmentioning
confidence: 99%
“…Two main reviews focused on VRT-based motor benefits [31,[107][108][109]. Consistent but explorative controlled randomized studies or pilot studies were included in these reviews, suggesting that VRT may promote functional recovery in patients with MS if coupled with robotic rehabilitation [110], improve the ability to perform daily activities [111][112][113], balance and gait [21,[114][115][116][117][118][119][120][121], increase short-term motor learning [122], upper limb functionality [112], and processing and integration of sensory information, with a positive impact on motor and cognitive [118,[123][124][125]; however, training differences emerged between VR-based and conventional intervention, but these were not robust when comparing VR-based intervention and passive intervention [21,[108][109][110][111][112][113][114][115][116][117][118][119][120][121].…”
Section: Multiple Sclerosismentioning
confidence: 99%